Measurement uncertainty and unicity of single number quantities describing the spatial decay of speech level in open-plan offices. (November 2021) - Lenne, Lucas; Chevret, Patrick; Parizet, Étienne
Abstract: The ISO 3382-3 standard (2012) defines single number quantities (SNQs) which evaluate the acoustic quality of open-plan offices, but does not address the issue of measurement uncertainties. This study focusses on the SNQs present in this standard related to spatial decay of speech, i.e. D2S, LpAS4m and rc . The aim is to provide additional information to the limited literature on the measurement uncertainties of these SNQs by use of both analytical developments and a stochastic approach based on simulations. The accuracy of the analytical developments was studied thanks to simulations of the sound propagation within a series of offices (1 layout, 16 acoustic configurations with different screen heights and different acoustic qualities of screens and ceiling). The SNQs obtained in the simulations cover a wide range: D2S between 3.4 and 7.5 dB(A), LpAS4m between 40.6 and 51.9 dB(A) and rc between 2.5 and 14.7 m. Therefore, the simulations are representative of a broad set of acoustic qualities. Estimated uncertainties have a magnitude of 0.4 dB(A) for D2S and vary between 0.4 and 0.7 dB(A) for LpAS4m and between 0.2 and 1.5 m for rc over a measurement path comprising 7 measurement positions. The simulations also raise the question of describing the acoustic quality of an office using a single value for the indicators. The results of the simulations show that in some cases, D2S values significantly depend on the measurement path, leading to a strong increase of its measurement uncertainty if a unique value is to be considered.